Indian Hand Anthropometry: First Web Space Angle Measurement in A Population of 800 Subjects - Parag B. Lad; Mukund R. Thatte; Maryada V. Reddy; Bipin Ghanghurde; Venkateshwaran N.; Ashish Phadnis (Indian Journal of Plastic Surgery)
Background The first web space of the hand plays a crucial role in determining the hand's span. Our study aims to examine and quantify the first web space angle in both hands of adult individuals within the Indian population with no upper limb pathologies. The primary objective of this study is to establish normative data. These data will be useful in surgical correction for the first web release, recommending corrective splints, and calculating the percentage of disability in hand function.